Compliance of Geriatric Patients with a History of Cardiovascular Disorders with Pre-Anesthesia Preparation - Dewi, Ni Nyoman Ari Kundari; Parwati, Atika; Suyasa, Agus Baratha; Devi, Ni Luh Putu Lusiana; Maharyawan, I Wayan Agus (Indonesian Journal of Global Health Research, 2025)
Geriatric patients undergoing surgical procedures are required to strictly comply with regulations related to pre-anesthetic preparation. Intraoperative and postoperative complications occur relatively frequently, particularly among elderly patients. To date, there has been limited research examining compliance with pre-anesthetic preparation among geriatric patients with a history of cardiovascular disorders. This study aimed to determine the level of compliance with pre-anesthetic preparation among geriatric patients with a history of cardiovascular disorders at Sanjiwani Regional General Hospital, Gianyar. This study employed a descriptive design with a cross-sectional approach. The sample was obtained using a consecutive sampling technique, with a sample size of 102 geriatric patients. The questionnaire used was a standard questionnaire with a Cronbach's Alpha value of 0.80. Data were collected using a questionnaire and analyzed using descriptive statistics. Result: The results showed that the majority of respondents had a moderate level of compliance with pre-anesthetic preparation, accounting for 64 respondents (62.7%), while 10 respondents (9.8%) demonstrated a low level of compliance. Collaboration among various parties is expected, not only involving healthcare professionals but also emphasizing the importance of family involvement, to improve patient compliance and ensure that surgical and anesthetic procedures during the intraoperative period can be carried out smoothly.